2016
DOI: 10.1016/j.cell.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

MOF Acetyl Transferase Regulates Transcription and Respiration in Mitochondria

Abstract: A functional crosstalk between epigenetic regulators and metabolic control could provide a mechanism to adapt cellular responses to environmental cues. We report that the well-known nuclear MYST family acetyl transferase MOF and a subset of its non-specific lethal complex partners reside in mitochondria. MOF regulates oxidative phosphorylation by controlling expression of respiratory genes from both nuclear and mtDNA in aerobically respiring cells. MOF binds mtDNA, and this binding is dependent on KANSL3. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 62 publications
5
136
0
Order By: Relevance
“…These modifications include lysine methylation, phosphorylation, acetylation, ubiquitylation, sumoylation, and PARylation (reviewed in Bannister and Kouzarides, 2011). The enzymatic acetylation inside mitochondria has been recently acknowledged as four acetyl transferases ACAT1, MOF, GCN5L1, and PCAF have been identified in the mitochondria and are responsible for regulation of acetylation levels of mitochondrial proteins (Fan et al, 2014;Chatterjee et al, 2016;Wang et al, 2017;Savoia et al, 2019). It is estimated that approximately 63% of proteins that are localized within the mitochondrion contain lysine acetylation sites, and in one study conducted in 2011, 216 phosphopeptides were identified from mitochondrial preparations (Zhao et al, 2011).…”
Section: Post-translational Modifications Of Mitochondrial Nucleoid Pmentioning
confidence: 99%
“…These modifications include lysine methylation, phosphorylation, acetylation, ubiquitylation, sumoylation, and PARylation (reviewed in Bannister and Kouzarides, 2011). The enzymatic acetylation inside mitochondria has been recently acknowledged as four acetyl transferases ACAT1, MOF, GCN5L1, and PCAF have been identified in the mitochondria and are responsible for regulation of acetylation levels of mitochondrial proteins (Fan et al, 2014;Chatterjee et al, 2016;Wang et al, 2017;Savoia et al, 2019). It is estimated that approximately 63% of proteins that are localized within the mitochondrion contain lysine acetylation sites, and in one study conducted in 2011, 216 phosphopeptides were identified from mitochondrial preparations (Zhao et al, 2011).…”
Section: Post-translational Modifications Of Mitochondrial Nucleoid Pmentioning
confidence: 99%
“…Interestingly, it was recently reported that the nuclear MYST family acetyl transferase MOF is also present in mitochondria where it binds mtDNA and regulates expression of OXPHOS genes from both, nDNA and mtDNA (Chatterjee et al , ). MOF deficiency resulted not only in mitochondrial dysfunction but also in hypertrophic cardiomyopathy and cardiac failure (Chatterjee et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
“…The PLA signal was localized on all chromosomes and was abundant in the cytoplasm, potentially reflecting mitochondrial MOF [7]. The ubiquitylated sites in the structured C-terminal half of the protein were qualitatively similar in male or female cells, and therefore not due to the action of the male-specific MSL2 E3 ligase.…”
Section: Discussionmentioning
confidence: 99%
“…the one that is chromosome-engaged at the X territories, and may escape detection because mass spectrometry approaches are highly biased towards abundant peptides. Conceivably, a fraction of MOF does not reside in the MSL-DCC but rather in NSL-type complexes, which regulate many promoters on all chromosomes as well as mitochondrial transcription in mammals [1,2,5,7]. MOF may be substrate of other E3 ligases (about 150 E3 ligases exist in Drosophila [36]), whose combined activities are likely to dominate ubiquitylation events in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation